2017
DOI: 10.2174/1381612822666161021124358
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Fractionation of Polyphenols by Membrane Operations

Abstract: Membrane technology is an excellent candidate to make a paradigm shift in biological active compounds fractionation/separation processes. Presented results clearly demonstrate that membrane processes are of great advantages over traditionally used methods; however, characterization of separated polyphenols has to be improved. Most of citied authors concentrated their investigation only on the total amount of polyphenols determination. Exhaustive studies including: antioxidant activities, retention index, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The concentration and selective fractionation of bioactive compounds from aqueous and alcoholic processing streams of agro-food production by pressure-driven membrane processes, including ultrafiltration (UF) and nanofiltration (NF), have been extensively studied in the last years [14,15,16]. These processes offer several advantages when compared with conventional separation methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration and selective fractionation of bioactive compounds from aqueous and alcoholic processing streams of agro-food production by pressure-driven membrane processes, including ultrafiltration (UF) and nanofiltration (NF), have been extensively studied in the last years [14,15,16]. These processes offer several advantages when compared with conventional separation methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that plant materials could contain up to 10.000 naturally occurring compounds belonging to the category of "phenolics" with different molecular weights (Mw) 35 . As Tsibranska and co-authors 16 reported, polyphenols with Mw higher than the membrane cut-off are retained on the membrane surface in dead-end filtration methods such as filtration sterilization, resulting in a loss of material. Indeed, the deep inspection of the filter surface with optical microscope after the extract sterilization put into evidence some dark spots (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…functional groups [13][14][15] . They are classified into the following groups: phenolic acids, flavonoids, lignans, curcuminoids, stilbenes, and tannins 16 . Recently, multiple studies have documented anticancer activity in phenolic acids and flavonoids, which has been attributed to their potent antioxidant and anti-inflammatory properties as well as their capabilities to modulate molecular targets and signaling pathways that have been associated with cell survival, decreased cell proliferation, increased apoptosis, suppression of angiogenesis, detoxification enzymes, immune responses, and many others 7,[17][18][19][20][21][22] .…”
mentioning
confidence: 99%
“…Continuous processes , and membrane-based separations can significantly improve the sustainability and economics of chemical manufacturing . The field of organic solvent nanofiltration (OSN) has significantly evolved over the past decade, and robust membranes are available for “in-line” solvent recycling, which can drastically reduce solvent consumption. OSN has recently been proposed for the fractionation of lignin, flavonoids, and polyphenol compounds. However, the obtained fractions contained a mixture of structurally similar compounds with similar molecular weights.…”
Section: Introductionmentioning
confidence: 99%